2016
DOI: 10.36965/ojakm.2016.4(2)128-145
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' attitudes toward the use of IoT medical devices as part of their practice

Abstract: The increasing number of patients using medical devices that are based on Internet of Things (IoT) technology presents physicians with a variety of challenges. The purpose of this exploratory research is to provide first insights into the way physicians perceive FDA approved IoT medical devices (IoT-MDs). A questionnaire was developed and improved after a pilot survey with the participation of 23 physicians. Data was collected from 126 physicians in 2014 and from another 50 in 2015, who answered the questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…One study employed a qualitative design through the use of focus groups (1.4%) [ 55 ], and representations of data collection methods. A mixed-method design was used in one study (1.4%) [ 46 , 54 ]. The rest of the studies did not mention the design methods they used [ 50 ].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…One study employed a qualitative design through the use of focus groups (1.4%) [ 55 ], and representations of data collection methods. A mixed-method design was used in one study (1.4%) [ 46 , 54 ]. The rest of the studies did not mention the design methods they used [ 50 ].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Attitude can be defined as afeeling or opinion regarding something or someone, or a way of behaving that is caused by something or someone. Achituv and Haiman [65] found that doctors held positive attitudes towards IoT-based medical devices, which meant that they were aware of and ready to use this technology. Kim [66] found that most IoT users show a positive attitude towards using IoT devices, and ascribe a greater quality to the information transmitted.…”
Section: F Attitude Toward Using Iotmentioning
confidence: 99%
“…More than 65% of the nurses said that mIoT would have an impact on the future of nursing in the hospital. Similarly, the study by [27] found that only 4.7% of the participants were against integrating mIoT in the hospital. Also, [30] conducted research with 450 doctors in Riyadh, KSA.…”
Section: Perceptions Including Potential Barriers and Facilitatorsmentioning
confidence: 88%
“…Research conducted by [26] concluded that 76% of 350 nurses in their study had little knowledge of IoT technology. Similarly, [27] suggested insufficient awareness of mIoT use among physicians. Further, [28] found that employees lacked knowledge regarding artificial intelligence (an essential component of IoT).…”
Section: Discussionmentioning
confidence: 99%